A game of subsidization or taxation for new technology adoption in international duopoly. - Hattori, Masahiko
The adoption of new technology by firms is important for the economic growth, particularly developing countries. However, depending on the values of various parameters about demand, production cost, and setup cost, the adoption of new technology by firms may be insufficient or excessive in less competitive industries from the point of view of social welfare. Then, subsidization or taxation policies by the governments are necessary. In this paper we present an analysis of subsidization or taxation for new technology adoption in a framework of international duopoly with differentiated goods.